Leadership Model in Improving Mine Inspector Performance: A Systematic Review - Suharyani, Yenny Dwi; Riyanto, Setyo; Saluy, Ahmad Badawy; Elmi, Farida (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The mining industry plays a pivotal role in the global economy, but it faces significant challenges related to occupational safety, regulatory compliance, and operational efficiency. Mine inspectors are essential in ensuring mining operations adhere to safety standards and regulations. The supervisors' leadership styles heavily influence these inspectors' performance. This systematic review examines the impact of leadership models—transformational, transactional, situational leadership, and Herzberg's two-factor theory—on mine inspector performance. Researchers have found that transformational leadership, characterized by inspiration and motivation, significantly enhances job performance, satisfaction, and commitment among employees. Transactional leadership, which focuses on supervision, organization, and performance through rewards and punishments, is effective at ensuring compliance and efficiency. Situational leadership emphasizes the need for leaders to adapt their style to their followers' developmental levels, promoting flexibility and responsiveness. Herzberg's two-factor theory differentiates between motivators and hygiene factors, highlighting the importance of job satisfaction in enhancing performance. The path-goal theory, which outlines the leader's role in clearing the path toward goals, also provides valuable insights. The review concludes that transformational leadership is particularly effective in improving mine inspector performance, but a combination of leadership styles tailored to specific situations and needs is essential for optimal results. This understanding can guide mining industry leaders in adopting strategies that enhance safety, compliance, and overall operational efficiency.